Search for excited and exotic electrons in the egamma decay channel in pp collisions at sqrt[s] = 1.96 TeV. - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We present a search for excited and exotic electrons (e(*)) decaying to an electron and a photon, both with high transverse momentum. We use 202 pb(-1) of data collected in pp collisions at sqrt[s] = 1.96 TeV with the Collider Detector at Fermilab II detector. No signal above standard model expectation is seen for associated ee(*) production. We discuss the e(*) sensitivity in the parameter space of the excited electron mass M(e(*)) and the compositeness energy scale Lambda. In the contact interaction model, we exclude 132 GeV/c(2)